Difusi Inovasi Aplikasi Identitas Kependudukan Digital (IKD) Dinas Kependudukan dan Pencatatan Sipil Kota Kendal (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
The Digital Population Identity (IKD) constitutes a pivotal government innovation aimed at transforming public services, yet its widespread adoption is impeded by disparities in digital literacy and inherent technical constraints. This community engagement activity, integrated with a participatory internship scheme, concentrates on analyzing and supporting the innovation diffusion trajectory executed by the Population and Civil Registration Department (Disdukcapil) of Kendal City. The adopted methodology employs a Participatory Action approach, strategically combined with a mobile service paradigm (jemput bola) across three designated urban villages: Langenharjo, Kebondalem, and Karangsari. Core interventions involved intensive, interpersonal socialization sessions and customized technical support for account activation. The assessment findings robustly suggest that the "jemput bola" model effectively leveraged interpersonal communication channels, thereby mitigating public skepticism and substantially elevating community involvement in IKD activation. While persistent challenges related to network instability and device incompatibility were observed, this direct, hands-on approach is ascertained as fundamentally crucial for achieving effective and equitable digital transformation at the local level.